Deciphering the factors influencing the discrepant fate of antibiotic resistance genes in sludge and water phases during municipal wastewater treatment. (October 2018) - Zhang, Junya; Yang, Min; Zhong, Hui; Liu, Mengmeng; Sui, Qianwen; Zheng, Libing; Tong, Juan; Wei, Yuansong
Graphical abstract: Highlights: Inversed A 2 O showed better ARGs reduction compared to other configurations. Background value of ARGs in A 2 O-MBR was provided. Longer SRT deteriorated the ARGs reduction in A 2 O-MBR effluent. The tetX in water phase and intI1 in sludge phase should be emphasized. Microbial community discrepancy contributed most to the variance the fate of ARGs. Abstract: The discrepant fate of antibiotic resistance genes (ARGs) in sludge and water phases was investigated in a municipal wastewater treatment plant, and a lab-scale A 2 O-MBR was operated to provide background value of ARGs. The influencing factors of ARGs including microbial community, co-selection from heavy metals, biomass and horizontal gene transfer were concerned. Results showed that iA 2 O (inversed A 2 O) showed better ARGs reduction, and longer SRT (sludge retention time) increased ARGs relative abundance while reduced the gene copies of ARGs in the effluent, but significantly increased the ARGs in sludge phase. Compared to background value, the most enriched ARG was tetX in water phase, while it was intI1 in sludge phase. There existed higher abundance of multi-resistant bacteria in sludge phase, and microbial community determined the fate of ARGs in both water and sludge phase, while the direct effects from horizontal gene transfer should not be overlooked especially in water phase.